A new anti-microbial combination prolongs the latency period, reduces acute histologic chorioamnionitis as well as funisitis, and improves neonatal outcomes in preterm PROM. (3rd March 2016) - Lee, JoonHo; Romero, Roberto; Kim, Sun Min; Chaemsaithong, Piya; Park, Chan-Wook; Park, Joong Shin; Jun, Jong Kwan; Yoon, Bo Hyun
Abstract: Objective : Antibiotic administration is a standard practice in preterm premature rupture of membranes (PROM). Specific anti-microbial agents often include ampicillin and/or erythromycin. Anaerobes and genital mycoplasmas are frequently involved in preterm PROM, but are not adequately covered by antibiotics routinely used in clinical practice. Our objective was to compare outcomes of PROM treated with standard antibiotic administration versus a new combination more effective against these bacteria. Study design : A retrospective study compared perinatal outcomes in 314 patients with PROM <34 weeks receiving anti-microbial regimen 1 (ampicillin and/or cephalosporins; n = 195, 1993–2003) versus regimen 2 (ceftriaxone, clarithromycin and metronidazole; n = 119, 2003–2012). Intra-amniotic infection/inflammation was assessed by positive amniotic fluid culture and/or an elevated amniotic fluid MMP-8 concentration (>23 ng/mL). Results : (1) Patients treated with regimen 2 had a longer median antibiotic-to-delivery interval than those with regimen 1 [median (interquartile range) 23 d (10–51 d) versus 12 d (5–52 d), p < 0.01]; (2) patients who received regimen 2 had lower rates of acute histologic chorioamnionitis (50.5% versus 66.7%, p < 0.05) and funisitis (13.9% versus 42.9%, p < 0.001) than those who had received regimen 1; (3) the rates of intra-ventricular hemorrhage (IVH) and cerebral palsy (CP) were significantly lower in patients allocated to regimen 2 than regimen 1 (IVH: 2.1% versus 19.0%, p < 0.001 and CP: 0% versus 5.7%, p < 0.05); and (4) subgroup analysis showed that regimen 2 improved perinatal outcomes in pregnancies with intra-amniotic infection/inflammation, but not in those without intra-amniotic infection/inflammation (after adjusting for gestational age and antenatal corticosteroid administration). Conclusion : A new antibiotic combination consisting of ceftriaxone, clarithromycin, and metronidazole prolonged the latency period, reduced acute histologic chorioamnionitis/funisitis, and improved neonatal outcomes in patients with preterm PROM. These findings suggest that the combination of anti-microbial agents (ceftriaxone, clarithromycin, and metronidazole) may improve perinatal outcome in preterm PROM.